Isolamento de Leptospira hardjo em rebanho bovino com problemas de reprodução - Maria Helena Franco Morais (1994)
The ocurrence of Leptospira hardjo was tested in a bovine dairy herd with reproduction problems. 132 animals (41,8%) had positive reactions to that serotype and to microagglutination rapid test. The first isolate and tipification of hardjo hardjoprajtino genotype (CTG) proves its presence in clinical cases of bovine leptospirosis in Brazil. The seroagglutination with the reference sample of hardjo (OMS) and with the Brazilian isolate were positive, respectively, in 40 and 26,9% of the tested animals. Cross reactions were found between hardjo and wolffi Hom the Sejroe serum group.